2015
DOI: 10.3906/bot-1406-45
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater algal diversity of the South-Tajik Depression in a high-mountainous extreme environment, Tajikistan

Abstract: The research on algal communities' response to altitude and altitude-related climatic conditions is sparse. So far, a full, accessible list of algae from the water bodies of the South-Tajik Depression has not been available. We compiled an algal species list of 1190 taxa that were revealed by us or listed in references in the South-Tajik Depression high-mountain rivers Kafirnigan, Vakhsh, Kyzylsu, Yakhsu, and Tairsu and in the lakes of its basin. The altitude gradient of the studied area is about 2500 m above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…4). Can be seen that the role of diatoms in aquatic habitats of the Pamir Mountains is significantly decreased with increasing of habitat altitude [15]. Similar distribution we revealed for the Caucasus Mountain algal diversity (Fig.…”
Section: Altitudinal Distributionsupporting
confidence: 85%
See 2 more Smart Citations
“…4). Can be seen that the role of diatoms in aquatic habitats of the Pamir Mountains is significantly decreased with increasing of habitat altitude [15]. Similar distribution we revealed for the Caucasus Mountain algal diversity (Fig.…”
Section: Altitudinal Distributionsupporting
confidence: 85%
“…Material for this study comes from the last twenty years of research in the rivers and lakes of Eurasia [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Study Area and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier we revealed altitude as one of the influencing factor on the level of habitats up to 2,600 m a.s.l. and also high latitude [24,25]. More of them, the index value that we calculated for the Pamir mineral springs algal communities was 1.24.…”
Section: Diversity and Ecology Of Algae And Cyanobacteriamentioning
confidence: 82%
“…Earlier, S. Barinova [24] found that the Willis curve can be used as criteria for fullness of species list because the distribution follows the hyperbolic shape in well-studied algal floras in Eurasia. Therefore, we can do floristic, taxonomic and ecological analysis for the diatom flora in the Artabel Lakes Nature Park and compare it to other high mountain lake floras in this region where the Willis proportion also closely follows the hyperbolic shape [24][25][26][27][28]. One of the important characteristics of the Artabel Lakes Nature Park diatom flora is the composition of the dominant algae genera.…”
Section: Physical and Chemical Analysismentioning
confidence: 99%